2018
DOI: 10.1155/2018/4125752
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Wireless Sensor Network for Automated Corrosion Prediction of Steel Reinforcement

Abstract: Corrosion is one of the key issues that affect the service life and hinders wide application of steel reinforcement. Moreover, corrosion is a long-term process and not visible for embedded reinforcement. Thus, this research aims at developing a self-powered smart sensor system with integrated innovative prediction module for forecasting corrosion process of embedded steel reinforcement. Vibration-based energy harvester is used to harvest energy for continuous corrosion data collection. Spatial interpolation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The scale factor is usually expressed in volts per g (V/g), e.g., in [27,29]. Yet, due to introducing Equation (5), which corresponds to the employed calibration procedure employing tilt angles as the reference, it is assumed that this parameter is expressed in volts in Equations (1)-(6), just like the offset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale factor is usually expressed in volts per g (V/g), e.g., in [27,29]. Yet, due to introducing Equation (5), which corresponds to the employed calibration procedure employing tilt angles as the reference, it is assumed that this parameter is expressed in volts in Equations (1)-(6), just like the offset.…”
Section: Resultsmentioning
confidence: 99%
“…Since their introduction to the market as detectors in automotive airbag systems in the 1980s, Microelectromechanical System (MEMS) accelerometers have been employed in an ever-increasing number of mechatronic and electronic systems. Whereas some modern applications, e.g., in smartphones [1] and the like (tablets, photo cameras, and smartwatches [2]), may not be so strategic, there are other devices, e.g., automotive safety systems like the said airbag or a new generation of motorcycle ABS [3], or even diving instruments [4], where MEMS accelerometers are directly responsible for the protection of human life-then, the related aging effects become as critical as the results of aging of, e.g., social infrastructures such as bridges and other essential infrastructure systems [5]; health monitoring of such structures is a solution increasing safety of their users [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [145] suggested a self-powered wireless sensor network for the automated prediction of steel reinforcement corrosion. The authors used self-powered wireless piezoelectric sensors.…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%
“…IoT-based corrosion monitoring system has advantages over wired sensors with datalogger systems in terms of continuous measurements, cost effectiveness, flexibility, remote monitoring, ease of deployment and maintenance. There have been proposals on the use of wireless sensor networks for corrosion detection [78][79][80][81] and IoT for structural health monitoring [73][74][75]. Among these works, Qiao et al [79], Sun et al [80], and Xu et al [81] employed IEEE802.15.4-based short-range connectivity for corrosion monitoring while Abdelgawad and Yelamarthi [74] used WiFi connectivity for structural health monitoring.…”
Section: Internet Of Things Based Corrosion Monitoringmentioning
confidence: 99%